A polymorphism and expression levels of SCD and their relationships to production traits in a Japanese farmed emu population - Yuichi Koshiishi; Suzuka Moriya; Yuki Ishida; Hiromitsu Ochiai; Kenta Wada (PLoS ONE, 2026)
The emu is a novel poultry species producing meat, eggs, and fat. In particular, emu oil derived from the fat is considered the most important product of the emu owing to its anti-inflammatory and anti-melanin production. Meanwhile, there are few reports on the genetic improvement of economic traits in emus. In this study, we discovered a non-synonymous substitution (c.267A > C, p.Leu89Phe) in the gene encoding stearoyl-CoA desaturase (SCD), a key enzyme involved in unsaturated fatty acid synthesis, in a Japanese farmed emu population. Although fat yields (fat weight per body weight) in males with AA and AC genotypes of SCD were higher than those in their female counterparts, significant intra-sex variations were not detected across genotypes in our study population. Moreover, fat melting points and fatty acid composition did not significantly vary between SCD genotypes. These results suggest that the SCD c.267A > C polymorphism does not affect fat production traits in emus. However, the expression levels of SCD transcripts were negatively correlated with fat content (P < 0.01) and positively correlated with meat yield (P < 0.05) in emus.